2016
DOI: 10.1080/14739879.2016.1245589
|View full text |Cite
|
Sign up to set email alerts
|

Educating about female genital mutilation

Abstract: Female genital mutilation (FGM) is illegal in the UK but nevertheless practised in some immigrant communities. Effective educational approaches are required to inform policy and to direct resources, often in the voluntary sector. The opinions in this article arise from discussions with professionals and members of FGM-practising communities. We highlight the importance of sharing experiences and expertise across health and social care professionals as well as working in partnership with culturally sensitive No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
5
0
2
Order By: Relevance
“…Another study conducted by Shabila et al [24] reported the necessity to include religious leaders in the FGC issue. Other studies concluded that the involvement of religious leaders would be critical in eradicating FGC [25,26]. However, our analysis revealed that some religious leaders highlighted the need to reach a conclusive answer concerning FGC to advise people accordingly.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Another study conducted by Shabila et al [24] reported the necessity to include religious leaders in the FGC issue. Other studies concluded that the involvement of religious leaders would be critical in eradicating FGC [25,26]. However, our analysis revealed that some religious leaders highlighted the need to reach a conclusive answer concerning FGC to advise people accordingly.…”
Section: Discussionmentioning
confidence: 54%
“…Another study conducted by Shabila et al [24] reported the necessity to include religious leaders in the FGC issue. Other studies concluded that the involvement of religious leaders would be critical in eradicating FGC [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…While the American College of Obstetricians and Gynecologist developed an educational program in 1999 and updated it in 2008, 8 and there have been calls in the medical literature to enhance educational initiatives, [9][10][11][12] there is still a woeful lack of education regarding FGC in both undergraduate and graduate medical education programs across the United States. Although data are somewhat limited, evidence suggests that American HCPs are not sufficiently prepared to provide comprehensive, culturally sensitive care to women and girls affected by FGC.…”
Section: A Widespread Practicementioning
confidence: 99%
“…Ülkemizde terim yaygın olmasa da, "kadın sünneti" ve "kız sünneti" eş anlamlı kullanılmaktadır. Hiç şüphesiz bu argümanların hiçbirinin bilimsel geçerliliği yoktur ve hepsi ancak birer "mit"tir (20).…”
Section: Kız çOcuklarda Ve Kadınlarda Sünnetunclassified
“…Ülkemizde terim yaygın olmasa da, "kadın sünneti" ve "kız sünneti" eş anlamlı kullanılmaktadır. (20).…”
Section: Kız çOcuklarda Ve Kadınlarda Sünnetunclassified